basic algebra n.
Download
Skip this Video
Loading SlideShow in 5 Seconds..
Explained by Ben Lozar PowerPoint Presentation
Download Presentation
Explained by Ben Lozar

Loading in 2 Seconds...

play fullscreen
1 / 6

Explained by Ben Lozar - PowerPoint PPT Presentation


  • 133 Views
  • Uploaded on

Basic Algebra. Explained by Ben Lozar. Finding X. 2 Variables. Finding X. Equation: 7x+5=26 Question: What is ‘x’? Answer: x = 3 How do you actually find x = 3? . What is ‘X’? 7x + 5 =26. First. Subtract 5 from both sides. 7x+5-5=26-5 7x = 21. Second. Divide by 7 on both sides

loader
I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.
capcha
Download Presentation

PowerPoint Slideshow about 'Explained by Ben Lozar' - belle


An Image/Link below is provided (as is) to download presentation

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.


- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript
finding x
Finding X
  • Equation:7x+5=26
  • Question:What is ‘x’?
  • Answer: x = 3
  • How do you actually find x = 3?
what is x 7x 5 26
What is ‘X’? 7x + 5 =26

First

Subtract 5 from both sides.

7x+5-5=26-5

7x = 21

Second

Divide by 7 on both sides

7x/7 = 21/7

Result: x =3

Action

Action

Result

Answer

two variables
Two Variables
  • Two Equations:

2x – 3y = 3

x – y = 5

  • How do we solve this?
  • 2 ways: Elimination or Substitution
elimination
Elimination

First Action

Multiply 1 or both equations to create opposite coefficients

5x – 3y = 3

-3(x – y) = -3(5)

5x – 3y = 3

-3x + 3y = -15

Add both equations together to ELIMINATE one variable and one equation

2x = -12

Something Familiar

Find x

2x/2 = -12/2

X = -6

Then, Substitute x into one of the equations to find y.

-6 –y = 5

-11 = y

X = 6

Y = -11

The Home Stretch

Result

Second Action

Answer

2

substitution
Substitution

First Step

Something familiar…again!

Solve for the remaining variable

7 = 5y

7/5 = y

Solve for the second variable by substituting the already solved variable

x = 5 – 7/5

x= 12/5

x = 12/5

y = 7/5

Solve 1 equation for either variable

x = 5 – y

Substitute what you got into the other equation

2(5-y) – 3y= 3

10 – 2y – 3y = 3

10 – 5y = 3

Second Step

The Home Stretch

Answer